Transport of montmorillonite colloid in unsaturated packed column: The combined effects of sand grain size, flow rate and colloid concentration - Zhang, Linlin; Zhu, Jun; Zhang, Qiulan; Shao, Jingli; Cui, Yali; Zhang, Aiming (Frontiers in Environmental Science, 2022)
The transport of colloid in unsaturated porous media affects the migration of contaminants and thus is closely related to groundwater resources protection. To figure out the combined effects of grain size, colloid concentration and injection flow rate on montmorillonite colloid transport characteristics in unsaturated quartz sand, a total of 27 sets of column experiments were conducted with three kinds of quartz sand (20, 40, 60 mesh), three flow rates (1.98, 3.96, 5.94 cm3/min) and three colloid concentrations (300, 600, 900 mg/L), using three packed columns with the inner diameter of 11cm and the height of 40 cm. The experimental results showed that the transport of Na-montmorillonite colloid particles in the unsaturated quartz sand columnoccurred with significant retention. In the 20 mesh quartz sand column, the average peak values of the penetration curves for low and high concentration colloidal solutions of 300 and 900 mg/L increased by 44% and 27%, respectively, as the flow rate increased from 1.98 to 5.94 cm3/min. The average peak value of the colloidal solution with concentration 300 mg/L increased 17% more than that of the colloidal solution with 900 mg/L for increasing flow rate. When the injection flow rate of the colloidal solution was increased from 1.98 to 5.94 cm3/min, the effect of flow rate on colloidal transport was the most obvious, followed by the effect of media particle size, while the effect of colloidal solution concentration was the least. The calculation based on the total potential energy of Derjaguin-Landau-Verwey-Overbeek (DLVO) and collision efficiency further explained the retention of colloids in unsaturated porous media.